2020
DOI: 10.1177/0958928720971094
|View full text |Cite
|
Sign up to set email alerts
|

Breadwinning or on the breadline? Female breadwinners’ economic characteristics across 20 welfare states

Abstract: In analysing heterosexual couples’ work–family arrangements over time and space, the comparative social policy literature has settled on the framework of the ‘male-breadwinner’ versus the ‘dual-earner’ family. Yet, in assuming men in couple-families are (full-time) employed, this framework overlooks another work–family arrangement, which is the ‘female-breadwinner’ couple. Including female-breadwinner couples matters because of their growing prevalence and, as our analysis shows, greater economic vulnerability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Crucially, and differently from Qian and Hu (2021), we distinguish between pure and modified female breadwinners, as the economic characteristics of these two couple types are essentially different (Kowalewska and Vitali 2021), and using these categories can give us a better understanding of possible signs of retraditionalisation in work patterns among partners.…”
Section: Data and Samplementioning
confidence: 99%
“…Crucially, and differently from Qian and Hu (2021), we distinguish between pure and modified female breadwinners, as the economic characteristics of these two couple types are essentially different (Kowalewska and Vitali 2021), and using these categories can give us a better understanding of possible signs of retraditionalisation in work patterns among partners.…”
Section: Data and Samplementioning
confidence: 99%
“…In order to understand the meaning of the breadwinner arrangement, we need to focus on the patterns of women and men separately. Previous studies have shown gender differences in how mixed unions are formed [ 71 ], and that the determinants of mixed unions and the meaning of a male breadwinner arrangement are different from those of a female breadwinner arrangement [ 64 ]. We found that the effects in the models were stronger for non-migrant men than for non-migrant women, especially for the unions with a non-European partner.…”
Section: Discussionmentioning
confidence: 99%
“…However, even if this arrangement is not the one that is preferred by the man and his migrant partner, the couple will try to achieve an economic situation and a household income that the partners can live on until the migrant partner can participate in the labor market in the desired way. This contrasts with the working and earning conditions of women and the negative effects of a female breadwinner model [ 64 ]. Therefore, this situation seems comparable to that of women in eastern Germany, who, on average, make larger contributions to the household income than women in western Germany [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas full-time employment -or at least long part-time employment -is common for women in Nordic countries, short part-time employment is widespread among women in most Anglo-Saxon and Continental countries. Meanwhile, although many women across post-Soviet countries, Southern Europe and the United States work full time, male breadwinning is also prevalent (Kowalewska and Vitali, 2020;Lewis et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%